An ETHYLENE RESPONSE FACTOR-MYB Transcription Complex Regulates Furaneol Biosynthesis by Activating QUINONE OXIDOREDUCTASE Expression in Strawberry. Issue 1 (9th July 2018) - Zhang, Yuanyuan; Yin, Xueren; Xiao, Yuwei; Zhang, Zuying; Li, Shaojia; Liu, Xiaofen; Zhang, Bo; Yang, Xiaofang; Grierson, Donald; Jiang, Guihua; Klee, Harry J.; Chen, Kunsong
Abstract : Fragaria × ananassa quinone oxidoreductase, which catalyzes the final step in furaneol biosynthesis in strawberry, is transcriptionally up-regulated by a complex consisting of an ethylene response factor and MYB during ripening. Abstract: 4-Hydroxy-2, 5-dimethyl-3(2H)-furanone is a major contributor to the aroma of strawberry ( Fragaria × ananassa ) fruit, and the last step in its biosynthesis is catalyzed by strawberry quinone oxidoreductase (FaQR). Here, an ethylene response factor (FaERF#9) was characterized as a positive regulator of the FaQR promoter. Linear regression analysis indicated that FaERF#9 transcript levels were correlated significantly with both FaQR transcripts and furanone content in different strawberry cultivars. Transient overexpression of FaERF#9 in strawberry fruit significantly increased FaQR expression and furaneol production. Yeast one-hybrid assays, however, indicated that FaERF#9 by itself did not bind to the FaQR promoter. An MYB transcription factor (FaMYB98) identified in yeast one-hybrid screening of the strawberry cDNA library was capable of both binding to the promoter and activating the transcription of FaQR by ∼5.6-fold. Yeast two-hybrid assay and bimolecular fluorescence complementation confirmed a direct protein-protein interaction between FaERF#9 and FaMYB98, and in combination, they activated the FaQR promoter 14-fold in transactivation assays. These results indicate that an ERF-MYB complex containing FaERF#9 and FaMYB98 activates the FaQR promoter and up-regulates 4-hydroxy-2, 5-dimethyl-3(2H)-furanone biosynthesis in strawberry.